Clinical efficacy, drug sustainability and serum drug levels in Crohn's disease patients treated with ustekinumab – A prospective, multicenter cohort from Hungary. Issue 2 (February 2022) - Gonczi, Lorant; Szanto, Kata; Farkas, Klaudia; Molnar, Tamas; Szamosi, Tamas; Schafer, Eszter; Golovics, Petra A.; Barkai, Laszlo; Lontai, Livia; Lovasz, Barbara; Juhasz, Mark; Patai, Arpad; et al.
Abstract: Introduction: Although efficacy of ustekinumab (UST) has been demonstrated through randomized trials, data from real-life prospective cohorts are still limited. Our aim was to evaluate clinical efficacy, drug sustainability, dose intensification and results from therapeutic drug monitoring in UST treated patients with Crohn's disease (CD) using a prospective, nationwide, multicenter cohort. Methods: Patients from 10 Inflammatory Bowel Disease centers were enrolled between 2019 January and 2020 May. Patient demographics, disease phenotype, treatment history, clinical disease activity (Crohn's Disease Activity Index(CDAI), Harvey Bradshaw Index(HBI)), biomarkers, and serum drug levels were obtained. Evaluations were performed at week8 (post-induction), w16–20, w32–36, and w52–56 follow-up visits. Results: A total of 142 patients were included [57.4% female; complex disease behavior (B2/B3):48%, previous anti-TNF exposition:97%]. Clinical response and remission rates after induction(w8) were 78.1% and 57.7% using CDAI, and 82.5% and 51.8% based on HBI scores. The one-year clinical remission rate was 58%/57.3%(CDAI/HBI). Composite clinical and biomarker remission (CDAI<150 and C-reactive protein<10 mg/L) rates were 35.4%; 33.3%; 38.6% and 36.6% at w8/w16–20/w32–36 and w52–56. Drug sustainability was 81.9%(standard deviation(SD): 3.4) at 1 year(1y). Probability of dose intensification was high and introduced early, 42.2%(SD:4.2) at ~w32 and 51.9%(SD:4.4%) at 1y. Conclusion: Ustekinumab showed favorable drug sustainability and clinical efficacy in a patient population with severe disease phenotype and previous anti-tumor necrosis factor (anti-TNF) failure, however frequent dose intensification was required.